Being in-between; exploring former cult members’ experiences of an acculturation process using the cultural formulation interview (DSM-5) - Hadding, Cecilia; Semb, Olof; Lehti, Arja; Fahlström, Martin; Sandlund, Mikael; DeMarinis, Valerie (Frontiers in Psychiatry, 2023)
Objective: To explore the experiences of acculturation into secular Swedish society of former members of cults, with particular focus on mental health, needs and resources.Design: Qualitative method using the Cultural Formulation Interview (CFI) from the DSM-5 as an interview guide. Analysis of participants' experiences of acculturation through systematic text condensation.Participants: Eleven Swedish former members of ideological or religion-based cults.Setting: Swedish mainstream, secular society.Results: Former cult members experience an 'in-between time' in the period after leaving the cult and find themselves in a confusing, chaotic state. They describe having lived in an honor culture where acts of violence were normalized. In the cult, they felt disconnected from themselves, and post-cult they try to regain access to their own values and feelings as well as create new bonds with family members and friends outside the cult. They find it hard to talk about their cult background and find relief in communicating with other former cult members.In their post-cult life, they eventually start seeing the world in a brighter, more hopeful way than before. However, they are also at risk of re-experiencing cult-related traumatic events and of new traumatic experiences within the post-cult acculturation process, and of persistent psychological distress.Conclusion: Former cult members face a challenging acculturation process, having lost a functioning worldview upon leaving the cult but not yet gained another to take its place.While the in-between time is often transient, they may need support from the healthcare system, especially regarding mental health concerns, while establishing themselves into mainstream society.